ANALISIS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM PRAKTIK PENGELOLAAN SEKOLAH DASAR - Hidayati, Nurul; Ahmad Thohirin; Suyitno (STKIP Subang, 2026)
This research aims to describe and analyze the principal's transformational leadership strategies in managing elementary schools at UPT Satuan Pendidikan SDN Tampung II and SDN Sumber Glagah, Rembang District. The main focus of this study is how principals who are graduates of the